Peningkatan Kapasitas Tutor PKBM Melalui Pelatihan Komunikasi Humanistik Dan Metode GASING Untuk Pembentukan Karakter Peserta Didik - Titi Hendrawati; Nurshiddieq (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
This community service activity aims to improve the capacity of PKBM tutors in applying humanistic communication and the GASING method to support students’ character development. The program was conducted at PKBM Bina Mandiri Cipageran Cimahi using the Participatory Action Research (PAR) approach through stages of needs assessment, training, mentoring, implementation, and evaluation. The implementation methods included workshops, learning practices, observations, participatory discussions, and mentoring activities for tutors in applying humanistic communication and the GASING method during the learning process. The results of the program showed an improvement in tutors’ understanding and skills in creating a more communicative, enjoyable, and student-centered learning environment. In addition, students demonstrated increased learning motivation, participation, discipline, self-confidence, and cooperation during classroom activities. This community service program also contributed positively to strengthening a humanistic learning culture within the PKBM environment. The implication of this activity indicates that continuous training and mentoring can become an effective empowerment model for non-formal education tutors in supporting sustainable character-based learning.